Holt's realism: new reasons for behavior analysis - Tonneau, François Jacques (2012)
Behavior analysts and ecological psychologists may be more aware than before of the commonalities between their respective approaches (Costall, 1984; Morris, 2009). It is time for behavior analysis to come back to its realist roots (O’Neil, 1968) and face the hard issue of perception